Genetic evaluation of short-term selection in synthetic coloured broiler male and female lines— Direct and correlated responses - REDDY, B L N; CHATTERJEE, R N; RAJKUMAR, U; NIRANJAN, M; RAJARAVINDRA, K S; BHATTACHARYA, T K (The Indian Journal of Animal Sciences, 2013)
Broiler male line (PB-1) and female line (PB-2) were under continuous mass selection for 6 week body weight and independent culling level was applied for 40 week egg production in female line. Data obtained over 5 generations on juvenile body weights and production traits was analyzed to evaluate the short-term direct and correlated responses in both lines. In male line, genetic responses for 6 WK body weight, 20 WK body weight,40WK body weight, age at sexual maturity,32 WK egg weight,40 WK egg weight and 40 WK egg production were 31.6±21.31 g, –80.10±111.98 g, –38.60±102.58 g, 0.50±2.31days, 0.24±2.40 g,-0.49±0.81 g and 1.80±4.69eggs respectively. On genetic scale 6 WK body weight was improved significantly (P<0.05). Body weight at 20 WK and 40 WK were decreased and there was a marginal gain in ASM and egg production up to 40 weeks of age. On phenotypic scale in male line, body weights at 6 WK, 20 WK and 40 WK were increased, but non-significant, while, ASM, egg weight at 32 and 40 weeks of age were decreased, but non-significant. Egg production to 40 weeks of age was improved significantly (P<0.05). In female line genetic responses for 6 WK body weight, 20 WK body weight, 40 WK body weight, ASM, 32 WK egg weight, 40 WK egg weight and 40 WK egg production were 32.22±12.55 g, –44.30±122.79 g, –78.70±28.29 g, 1.70±2.99days, -0.09±0.73 g, 0.61±0.71 g and 0.35±2.92eggs respectively. On genetic scale 6 WK body weight was improved but non-significant. Body weight at 20 WK, 40 WK and egg weight at 32 WK were decreased, but non-significant. There was marginal genetic gain in ASM, 40 WK egg weight and 40 WK egg production. On phenotypic scale in female line body weights at 6WK, 20WK and 40WK were improved, but non-significant, while egg production was improved significantly (P<0.05), ASM and egg weight at 32 WK and 40WK were decreased, but non-significant